Curvature dependence of quantum gravity with scalars - Bürger, Benjamin; Pawlowski, Jan M.; Reichert, Manuel; Schaefer, Bernd-Jochen (Arxiv, 2019)
We compute curvature-dependent graviton correlation functions and couplings as well as the full curvature potential $f(R)$ in asymptotically safe quantum gravity coupled to scalars. The setup is based on a systematic vertex expansion about metric backgrounds with constant curvatures initiated in arXiv:1711.09259 for positive curvatures. We extend these results to negative curvature and investigate the influence of minimally coupled scalars. The quantum equation of motion has two solutions for all accessible numbers of scalar fields. We observe that the solution at negative curvature is a minimum, while the solution at positive curvature is a maximum. We find indications that the solution to the equation of motions for scalar-gravity systems is at large positive curvature, for which the system might be stable for all scalar flavours.